Question
upstudy study bank question image url

\( \lim _{x \rightarrow-=} \frac{x^{2}-x^{2}+x}{x^{3}-x+5} \)

Ask by Bond Moreno. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The limit is 0.

Solution

Calculate the limit \( \lim_{x\rightarrow -\infty} \frac{x^{2}-x^{2}+x}{x^{3}-x+5} \). Evaluate the limit by following steps: - step0: Evaluate using transformations: \(\lim _{x\rightarrow -\infty}\left(\frac{x^{2}-x^{2}+x}{x^{3}-x+5}\right)\) - step1: Calculate: \(\lim _{x\rightarrow -\infty}\left(\frac{x}{x^{3}-x+5}\right)\) - step2: Rewrite the expression: \(\lim _{x\rightarrow -\infty}\left(\frac{x}{x^{3}}\times \frac{1}{1-\frac{1}{x^{2}}+\frac{5}{x^{3}}}\right)\) - step3: Calculate: \(\lim _{x\rightarrow -\infty}\left(\frac{1}{x^{2}}\times \frac{1}{1-\frac{1}{x^{2}}+\frac{5}{x^{3}}}\right)\) - step4: Rewrite the expression: \(\lim _{x\rightarrow -\infty}\left(\frac{1}{x^{2}}\right)\times \lim _{x\rightarrow -\infty}\left(\frac{1}{1-\frac{1}{x^{2}}+\frac{5}{x^{3}}}\right)\) - step5: Calculate: \(\lim _{x\rightarrow -\infty}\left(\frac{1}{x^{2}}\right)\times \frac{\lim _{x\rightarrow -\infty}\left(1\right)}{\lim _{x\rightarrow -\infty}\left(1-\frac{1}{x^{2}}+\frac{5}{x^{3}}\right)}\) - step6: Rewrite the expression: \(\lim _{x\rightarrow -\infty}\left(\frac{1}{x^{2}}\right)\times \frac{1}{\lim _{x\rightarrow -\infty}\left(1-\frac{1}{x^{2}}+\frac{5}{x^{3}}\right)}\) - step7: Rewrite the expression: \(\lim _{x\rightarrow -\infty}\left(\frac{1}{x^{2}}\right)\times \frac{1}{1}\) - step8: Rewrite the expression: \(0\times \frac{1}{1}\) - step9: Calculate: \(0\times 1\) - step10: Calculate: \(0\) The limit of the expression \( \frac{x^{2}-x^{2}+x}{x^{3}-x+5} \) as \( x \) approaches negative infinity is 0.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To evaluate the limit \( \lim _{x \rightarrow 0^{-}} \frac{x^{2}-x^{2}+x}{x^{3}-x+5} \), we first simplify the expression. The numerator simplifies to \( x \) because \( x^{2}-x^{2} = 0 \). Therefore, the limit becomes: \[ \lim _{x \rightarrow 0^{-}} \frac{x}{x^{3}-x+5} \] Now, we can substitute \( x = 0 \) in the denominator: \[ x^{3} - x + 5 = 0^{3} - 0 + 5 = 5 \] Thus, the limit now looks like: \[ \lim _{x \rightarrow 0^{-}} \frac{x}{5} = \frac{0}{5} = 0 \] Therefore, the final result is: \[ \lim _{x \rightarrow 0^{-}} \frac{x^{2}-x^{2}+x}{x^{3}-x+5} = 0 \]

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy